LEGAL LIABILITY OF INTERACTIVE DIGITAL GAME PLATFORMS FOR VIRTUAL TRANSACTIONS BY MINORS - Gunsu Nurmansyah (PRANATA HUKUM, 2026)
The rapid rise of interactive digital games has led to virtual transactions in which players purchase in-game items with real money. This becomes problematic when children, as dominant users without legal capacity, are involved. Game designs often exploit microtransactions and loot boxes that trigger impulsive spending, making children targets of economic exploitation. This study examines the legal liability of digital game platform providers under Government Regulation No. 17 of 2025, which implements Articles 16A (5) and 168(3) of the 2024 ITE Law. Using a normative juridical approach, the study analyzes regulations and literature. Findings highlight the need for stronger platform obligations, including age verification, parental consent, bans on covert practices, and tiered sanctions. Active state regulation and collaboration with platforms, parents, and society are crucial to ensuring a safe and child-friendly digital environment.